The Implementation of Merdeka Curriculum based on Teacher’s Perception - Kulsum, Eva Meidi; Suloso, Luluk Wiji Asti (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to determine teachers’ perception in implementing Merdeka Curriculum. This research uses a qualitative descriptive method by distributing questionnaire and conducting semi-structured interviews. This research was conducted at SMA 1 Rancaekek. The participants in this study were four English teachers who had experience in teaching English using Merdeka Curriculum. The results both from questionnaire and interview show that English teachers had positive perceptions of the implementing the Merdeka Curriculum. The data results from the questionnaire which were supported by interview are divided into 5 indicators. First, launch of Merdeka Curriculum. Second, Merdeka Curriculum priority stage. Third, design principles and implementation mechanism of Merdeka Curriculum. Fourth, direction of change in Merdeka Curriculum. Fifth, structure and framework of Merdeka Curriculum. Therefore, in implementing learning in the classroom, teachers are free to design their own methods and strategies. Even though English teachers have positive perceptions, in practice they still need to adapt to this new policy as they said from the interview results.